Electron transfer in a supramolecular associate of a fullerene fragment - Krick Calderon, Rafael; Gallego, Maria; Calbo, Joaquin; Arago, Juan; Calderon, Rafael M. Krick; Liquido, Fernando H.; Iwamoto, Takahiro; Greene, Allison K.; Jackson, Edward A.; Perez, Emilio M.; Orti, Enrique; Guldi, Dirk Michael; et al. (Angewandte Chemie International Edition, 2014)
Herein, we investigate the association of a fullerene fragment, hemifullerene CH, with an electron-donating bowl-shaped tetrathiafulvalene derivative (truxTTF). UV/Vis titrations and DFT calculations support formation of the supramolecular complex, for which an association constant of log K=3.6±0.3 in CHCl at room temperature is calculated. Remarkably, electron transfer from truxTTF to CH to form the fully charge-separated species takes place upon irradiation of the associate with light, constituting the first example in which a fullerene fragment mimics the electron-accepting behavior of fullerenes within a supramolecular complex. Copyright © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.